Inflammation-Immunity-Nutrition Score: A Novel Prognostic Score for Patients with Resectable Colorectal Cancer - Li XY; Yao S; He YT; Ke SQ; Ma YF; Lu P; Nie SF; Wei SZ; Liang XJ; Liu L (Dove Medical Press, 2021)
Xin-Ying Li,1 Shuang Yao,1 Yang-Ting He,1 Song-Qing Ke,1 Yi-Fei Ma,2 Ping Lu,3 Shao-Fa Nie,1 Shao-Zhong Wei,2 Xin-Jun Liang,3 Li Liu1 1Department of Epidemiology and Biostatistics, The Ministry of Education Key Laboratory of Environment and Health, School of Public Health, Huazhong University of Science and Technology, Wuhan, People's Republic of China; 2Department of Gastrointestinal Oncology Surgery, Hubei Cancer Hospital, The Seventh Clinical School Affiliated of Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People's Republic of China; 3Department of Abdominal Oncology, Hubei Cancer Hospital, The Seventh Clinical School Affiliated of Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People's Republic of ChinaCorrespondence: Li LiuDepartment of Epidemiology and Biostatistics, the Ministry of Education Key Laboratory of Environment and Health, School of Public Health, Huazhong University of Science and Technology, Wuhan, People's Republic of ChinaTel/Fax +86-27-83693763Email liul2012@hust.edu.cnXin-Jun LiangDepartment of Abdominal Oncology, Hubei Cancer Hospital, The Seventh Clinical School Affiliated of Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People's Republic of ChinaTel/Fax +86-27-87671663Email doctorlxj@163.comPurpose: This study was designed to investigate the prognostic value of the combination of high-sensitivity C-reactive protein, lymphocyte, and albumin in patients with resectable colorectal cancer.Patients and Methods: Seven-hundred-and-nineteen patients who underwent colorectal cancer resection in Hubei Cancer Hospital were included. Inflammation-Immunity-Nutrition score (0- 6) was constructed based on preoperative high-sensitivity C-reactive protein, lymphocyte, and albumin. Time-dependent receiver operating characteristic curve, decision curve, Kaplan-Meier survival curve, Cox regression, and C-index were conducted to detect the prognostic values of inflammation-immunity-nutrition score. The prognostic values of inflammation-immunity-nutrition score in different subgroups by sex, location of tumor, pathologic stage, and KRAS mutation were also explored. The prognostic performance of inflammation-immunity-nutrition score was further compared with that of other traditional prognostic indicators.Results: The median follow-up time was 40 months. High inflammation-immunity-nutrition score (> 2 scores) presented worse survival, with the adjusted hazard ratios (95% confidence intervals) of 3.106 (2.202- 4.380) for overall survival and 2.105 (1.604- 2.764) for disease-free survival. Besides, the associations of high inflammation-immunity-nutrition score with overall survival were even stronger in cases with wild type KRAS, with the adjusted hazard ratios (95% confidence intervals) of 4.018 (2.355- 6.854). Considering the AUCs, C-indices, and hazard ratios estimates, inflammation-immunity-nutrition score presented better prognostic performance than high-sensitivity modified Glasgow prognostic score, high-sensitivity C-reactive protein to albumin ratio, prognostic nutrition index, carcinoembryonic antigen, and carbohydrate antigen 19-9 for overall survival.Conclusion: Inflammation-immunity-nutrition score might serve as a powerful prognostic score in patients with colorectal cancer for overall survival, particularly in patients with wild type KRAS.Keywords: high-sensitivity C-reactive protein, survival, colorectal cancer, inflammation